Facets of phylodiversity: evolutionary diversification, divergence and survival as conservation targets. (7th January 2019) - Kling, Matthew M.; Mishler, Brent D.; Thornhill, Andrew H.; Baldwin, Bruce G.; Ackerly, David D.
Abstract : Biodiversity is often described as having multiple facets, including species richness, functional diversity and phylogenetic diversity. In this paper, we argue that phylogenetic diversity itself has three distinct facets—lineage diversification, character divergence and survival time—that can be quantified using distinct branch length metrics on an evolutionary tree. Each dimension is related to different processes of macroevolution, has different spatial patterns and is tied to distinct goals for conserving biodiversity and protecting its future resilience and evolutionary potential. We compared the landscapes identified as top conservation priorities by each of these three metrics in a conservation gap analysis for California, a world biodiversity hotspot, using herbarium data on the biogeography and evolutionary relationships of more than 5000 native plant species. Our analysis incorporated a novel continuous metric of current land protection status, fine-scale data on landscape intactness and an optimization algorithm used to identify complementary priority sites containing concentrations of taxa that are evolutionarily unique, vulnerable due to small range size and/or poorly protected across their ranges. Top conservation priorities included pockets of coastal and northern California that ranked highly for all three phylodiversity dimensions and for species richness, as well as sites uniquely identified by each metric whose value may depend on whether properties such as genetic divergence, high net diversification or independent survival experience are most desirable in an Anthropocene flora. This article is part of the theme issue 'Biological collections for understanding biodiversity in the Anthropocene'.